Analisis Perencanaan Manajemen Resiko Bisnis Pada Sales Marketing Otomotif - Prabowo, Ilham; Yuwono, Wisnu (Jurnal Bangkit Indonesia, 2023)
An important component of a company's marketing plan for success is a risk management study. This essay aims to conduct a sales and marketing risk management study in the automotive industry, which competes in a dynamic and competitive consumer products market. The study is based on a descriptive contextual approach to analysis, which uses semi-structured interviews and observation of sales and marketing operations. According to the findings, market risk, competitor risk, regulatory risk, technology risk, and operational risk are the main risks that businesses must face in terms of sales and marketing. The article concludes by outlining a risk management strategy that includes discovering, evaluating, minimizing, and monitoring these risks.